INTEGRATION OF DIGITAL TECHNOLOGIES INTO THE RISK MANAGEMENT ACCOUNTING SYSTEM USING FINANCIAL INSTRUMENTS - Карзун, Данііл (Journal of Strategic Economic Research, 2025)
The article examines the accounting and organizational aspects of risk management in enterprises and companies using modern financial instruments. The purpose of the article is to form directions for the possible integration of digital technologies into the accounting system of financial instruments of enterprises and companies, taking into account the requirements of modern risk-oriented management, in order to increase the efficiency and effectiveness of the processes of identification, assessment and minimization of financial risks. Particular attention is paid to analyzing the essence of the concept of “risk” in the context of the financial activities of economic entities, and the main types of financial threats that can affect the stability and efficiency of enterprises are identified. The necessity of forming an effective risk management system is substantiated, in which financial instruments, in particular derivatives, play a key role, allowing not only to identify potential risks, but also to effectively neutralize or minimize them. Special attention is paid to the integration of digital technologies into the accounting and management of financial instruments, which significantly transforms modern accounting systems. Digital innovations are considered that ensure the automation of processes for collecting, processing, and analyzing financial information, increase the accuracy of risk assessment, ensure the efficiency of management decisions, and transparency of reporting. The article analyzes modern digital solutions in the field of risk management, in particular artificial intelligence systems, blockchain, cloud accounting platforms, and big data technologies that are being implemented in accounting and risk management practices. The results of the study are of practical importance for financial analysts, accountants, managers, and risk management specialists.